The Influence of Brand Image, Positive Word Of Mouth, and Social Media Promotion on Dessert Box Purchase Decisions - Harmadi, Desya Natalia; Rizal, Alimuddin (inovator, 2024)
The purpose of this study was to discover the impact of brand image, positive word of mouth, and social media promotion on dessert box purchasing decisions. This study was conducted on consumers of Kamei Kitchen Semarang. This study uses a purposive sampling method with the criteria of people who have bought and consumed the Kamei Kitchen Semarang dessert box. The number of respond- ents who were determined for this study were 95 people. With the help of the SPSS statistical program version 25.0, it can be seen the relationship between variables using multiple linear regression analysis.The results obtained from this study indicate that, firstly, although the brand image variable has a positive regression coefficient value but this variable does not significantly affect purchasing decisions, the second positive word of mouth variable has a positive and significant effect on purchasing decisions, the three variables of social media promotion have a positive and significant effect on purchasing decisions.